1995
DOI: 10.1159/000098744
|View full text |Cite
|
Sign up to set email alerts
|

Epidural Spinal Cord Stimulation in the Management of Spasms in Spinal Cord Injury: A Prospective Study

Abstract: Forty-eight spinal cord injury victims were implanted with an epidural spinal cord stimulation system to treat spasms that had not satisfactorily responded to medical therapy. All the patients were at least 6 months after the injury. The protocol included assessment by independent examiners preoperatively and at 3, 6, 12 and 24 months after the implant. Pre- and postoperative data collection included the frequency and severity of the spasms. Combining the frequency and intensity scores into a ‘severity’ score … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
31
1
5

Year Published

2000
2000
2022
2022

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 51 publications
(40 citation statements)
references
References 0 publications
2
31
1
5
Order By: Relevance
“…9,10,13,15,48 When baclofen binds to GABA B receptors both presynaptically and postsynaptically, monosynaptic and polysynaptic spinal reflexes are inhibited. 9,10,13,15,44 Upon binding of baclofen presynaptically, influx of calcium into the presynaptic terminal is restricted and neurotransmitter release in excitatory spinal pathways is decreased, leading to a decrease in alpha motor neuron activity. 9,10,15,34,49 When baclofen binds to GABA B receptors on the postsynaptic membrane of a Ia afferent, potassium channels allow the flow of potassium out of the Ia afferent terminal, resulting in membrane hyperpolarization and, hence, interruption of action potential transmission.…”
Section: Pharmacologic Managementmentioning
confidence: 99%
See 2 more Smart Citations
“…9,10,13,15,48 When baclofen binds to GABA B receptors both presynaptically and postsynaptically, monosynaptic and polysynaptic spinal reflexes are inhibited. 9,10,13,15,44 Upon binding of baclofen presynaptically, influx of calcium into the presynaptic terminal is restricted and neurotransmitter release in excitatory spinal pathways is decreased, leading to a decrease in alpha motor neuron activity. 9,10,15,34,49 When baclofen binds to GABA B receptors on the postsynaptic membrane of a Ia afferent, potassium channels allow the flow of potassium out of the Ia afferent terminal, resulting in membrane hyperpolarization and, hence, interruption of action potential transmission.…”
Section: Pharmacologic Managementmentioning
confidence: 99%
“…9,10,13,15,34,48 The result is interference with excitation-contraction coupling that is necessary to produce muscle contraction. 10,44 It has also been suggested that dantrolene may alter muscle spindle sensitivity by acting on the gamma motor neurons. 9,34 Dantrolene appears to have a greater effect on phasic than on tonic stretch reflexes and on fast twitch rather than slow twitch muscle fibers, with the clinical significance of these discrepancies remaining unclear.…”
Section: Pharmacologic Managementmentioning
confidence: 99%
See 1 more Smart Citation
“…9 This ®nding was again con®rmed by Barolat et al who, based on a total of 48 patients, concluded that SCS applied below the level of the lesion was an eective and safe approach to controlling SCI-related spasms. 10 The 1990s saw the interest in this approach declining, mainly due to technical problems and the realization that SCS as a method to control spasticity was less eective in patients with severe spasms of the lower limbs. 10,11 At the same time, however, SCS has established itself as a widely used method of controlling neurogenic pain, which is particularly eective if the induced paresthesia coincides with the area of pain distribution within the body.…”
Section: Introductionmentioning
confidence: 99%
“…10 The 1990s saw the interest in this approach declining, mainly due to technical problems and the realization that SCS as a method to control spasticity was less eective in patients with severe spasms of the lower limbs. 10,11 At the same time, however, SCS has established itself as a widely used method of controlling neurogenic pain, which is particularly eective if the induced paresthesia coincides with the area of pain distribution within the body. 12 In our earlier work on the subject of motor control in human SCI we have described the complex neurocontrol mechanisms of the lumbar cord below the level of injury, illustrating the dependence of motor control of the injured spinal cord on residual supraspinal input.…”
Section: Introductionmentioning
confidence: 99%